2013
DOI: 10.1371/journal.pone.0057307
|View full text |Cite
|
Sign up to set email alerts
|

CNS-Targeted Production of IL-17A Induces Glial Activation, Microvascular Pathology and Enhances the Neuroinflammatory Response to Systemic Endotoxemia

Abstract: Interleukin-17A (IL-17A) is a key cytokine modulating the course of inflammatory diseases. Whereas effector functions of IL-17A like induction of antimicrobial peptides and leukocyte infiltration could clearly be demonstrated for peripheral organs, CNS specific effects are not well defined and appear controversial. To further clarify the functional significance of IL-17A in the CNS, we generated a transgenic mouse line with astrocyte-restricted expression of the IL-17A gene. GFAP/IL-17A transgenic mice develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 90 publications
(100 reference statements)
2
44
0
Order By: Relevance
“…We found that IL-17A alone was able to drive a psoriatic response in the skin [12] that led to an associated cardiovascular disease [37]. Similarly, Müller et al [101] overexpressed IL-17A as a transgene driven by the GFAP promoter specific for astrocytes in the CNS. Placing IL-17A in high levels in the CNS proved informative: the authors found that IL-17A expression alone was able to activate glial cells and enhance neuroinflammatory responses, thus showing that CNS cells express a functional IL-17RA/C receptor complex.…”
Section: Il-17 Function In the Cnsmentioning
confidence: 56%
“…We found that IL-17A alone was able to drive a psoriatic response in the skin [12] that led to an associated cardiovascular disease [37]. Similarly, Müller et al [101] overexpressed IL-17A as a transgene driven by the GFAP promoter specific for astrocytes in the CNS. Placing IL-17A in high levels in the CNS proved informative: the authors found that IL-17A expression alone was able to activate glial cells and enhance neuroinflammatory responses, thus showing that CNS cells express a functional IL-17RA/C receptor complex.…”
Section: Il-17 Function In the Cnsmentioning
confidence: 56%
“…As well, using linear regression, IL-17 is a significant predictor for unchanged cases. Chronic IL-17 exposure can induce chronic vascular changes such as basement membrane thickening without a loss of integrity of the blood-retinal barrier [16]. These changes may impede the effect of VEGF inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of AEG-1 as a downstream target of IL-1β and TNF-α, along with its regulation of NF-κB signaling, implies that AEG-1 is a key component of autocrine inflammatory signaling in astrocytes. Astrocyte production of IL-17A, IL-6, IL-12 and CXCL10 induce significant neuroglial activation (Pagenstecher et al , 2000; Zimmermann et al , 2013). Disrupting astrocyte-derived inflammatory signaling and cytokine production in a rat model of neuroinflammation, resulted in attenuated neuro/glial activation (Soliman et al , 2013).…”
Section: Aeg-1 In Handmentioning
confidence: 99%